Electrochemical investigation on porphyrazines with peripheral crown-ether groups - KOCA, ATIF (SPRINGER WIEN, 2003)
In this study, the electrochemical properties of novel porphyrazines with eight crown ether substituents appending on the periphery through flexible chains were investigated by using cyclic voltammetry and controlled potential coulometry. Cyclic voltammetry measurements showed that the metal free porphyrazine gave all of the six possible redox reactions of common porphyrazine derivatives. Cobalt porphyrazine exhibited a metal-based reduction and a metal-based oxidation processes followed by two ligand-based reduction and two oxidation processes. I-p vs. nu(1/2) plots of redox processes of the two compounds indicated the diffusional mass transfer mechanism of the complexes. Copper porphyrazine gave an oxidation process having adsorption properties and three reduction reactions. The variations of peak current ratios of electrochemical reactions for all three complexes with scan rate showed that electron transfer processes of complexes were followed by reversible or irreversible chemical reactions. Aggregation and sandwich adduct formation properties of complexes were determined by CV measurements. Peak potentials of redox processes for all complexes were shifted towards positive potentials by addition of alkali metal cations. Addition of K+ formed sandwich type adducts with 15-crown-macrocycles diminishing aggregation of planar molecules by intramolecular rather than intermolecular complexation.
Keywords: electrochemistry; cobalt; copper; porphyrazines; crown ether; METAL-FREE; PHTHALOCYANINES; AGGREGATION; DERIVATIVES; ADSORPTION; CHEMISTRY; CARBON